Kinetic and kinematic analysis of stamping impacts during simulated rucking in rugby union - Oudshoorn, B. Y.; Driscoll, H. F.; Dunn, M.; James, D. (Journal of Sports Sciences, 2018)
Laceration injuries account for up to 23% of injuries in rugby union. They are frequently caused by studded footwear as a result of a player stamping onto another player during the ruck. Little is known about the kinetics and kinematics of rugby stamping impacts; current test methods assessing laceration injury risk of stud designs therefore lack informed test parameters. In this study, twelve participants stamped on an anthropomorphic test device in a one-on-one simulated ruck setting. Velocity and inclination angle of the foot prior to impact was determined from high-speed video footage. Total stamping force and individual stud force were measured using pressure sensors. Mean foot inbound velocity was 4.3 m/s (range 2.1-6.3 m/s). Mean peak total force was 1246 N and mean peak stud force was 214 N. The total mean effective mass during stamping was 6.6 kg (range: 1.6-13.5 kg) and stud effective mass was 1.2 kg (range: 0.5-2.9 kg). These results provide representative test parameters for mechanical test devices designed to assess laceration injury risk of studded footwear for rugby union.